If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x-9)-(x+2)(x-9)=0
We multiply parentheses
5x-(x+2)(x-9)-45=0
We multiply parentheses ..
-(+x^2-9x+2x-18)+5x-45=0
We get rid of parentheses
-x^2+9x-2x+5x+18-45=0
We add all the numbers together, and all the variables
-1x^2+12x-27=0
a = -1; b = 12; c = -27;
Δ = b2-4ac
Δ = 122-4·(-1)·(-27)
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{36}=6$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-6}{2*-1}=\frac{-18}{-2} =+9 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+6}{2*-1}=\frac{-6}{-2} =+3 $
| 5.6+.4-r=-5 | | 3v=(-6v5) | | 1/5x-1/5=2 | | 12x+24=12x+9+15 | | x=4-8+2 | | -12(2/3z)=2/5 | | 3/2x-5=2/x+3 | | 3(x-5.2)+7.6=20 | | 16x+8-8=32 | | (2-x)=(2x-3) | | 14-4b=b-1 | | 6+4(4x-6)=6-3(2x+1) | | x-9/5+9/5=-x/2 | | 0.625(x+10)-10=0 | | 5x/6-1/2=1/3 | | 6*7/12=x | | 1.5•4q-2=4 | | 1.8z+54=1.8 | | x/5+6x=4 | | T(x)=3/2x^2-3x-1 | | 2q+4=-8+8q-6 | | N-3=9-5n | | 13t-7=2 | | w-32=16+2 | | X+3/3+2x+1/12=7/8 | | h/9–12=-4 | | 1/4(2(x-1)+10)=x | | -x+(9/5)x=(7/5) | | w-32=16+ | | m-4×2m=8m | | 3(2x-2)=4(x+1) | | 7=12y |